Current Trends in Slavery Studies in Brazil - Conermann, Stephan; Dias Paes, Mariana; Hofmeister Pich, Roberto; Cruz Terra, Paulo (Dependency and Slavery Studies, 2023)
Slavery Studies are one of the most consolidated fields in Brazilian historiography with various discussions on issues like slave agency, slavery and law, slavery and capitalism, slave families, demography of slavery, transatlantic slave trade, abolition etc. Taking into consideration these new trends of Brazilian slavery studies, this volume of collected articles allows leading scholars to present their research to a broader academic community.